A review of the Himalayan genus Trypheridium Brancucci (Coleoptera: Cantharidae: Chauliognathinae) with description of a new species - Zubair, R.M.; Maqbool, Amir; Wachkoo, Aijaz Ahmad; Biffi, Gabriel (European Journal of Taxonomy, 2021)
The genus Trypheridium Brancucci, 1985 is endemic to the Hindu Kush Himalayan Region, and is currently known from a single species, T. nuristanicum (Wittmer, 1956). Here, the genus is reviewed, T. nuristanicum nom. emend. is re-described and T. kashmiricum sp. nov. is described from Kashmir Himalayan Region of India. Descriptions, diagnoses, high quality images, distribution maps and identification keys are presented. The morphology and distribution of Trypheridium are discussed and compared with those of the closely related genus Trypherus LeConte, 1851.